Literature Review : Implementasi Sistem Pakar Untuk Diagnosa Penyakit Diabetes Menggunakan Metode Fuzzy - Rahman Maulana; Muhammad Akbar Fadillah; Sakha Satrio Pambudi; Perani Rosyani (CV. Shofanah Media Berkah, 2023)
This research is a literature review aimed at exploring the implementation of expert systems using fuzzy logic in the diagnosis process of diabetes. Diabetes is a primary concern in the field of healthcare due to its significant impact on human well-being. Through a literature review, this research conducted a search and analysis of various relevant sources and scientific articles to elucidate the application of expert systems with fuzzy logic in diagnosing diabetes. The findings of the literature review demonstrate that the implementation of expert systems using fuzzy logic has successfully yielded positive outcomes in supporting the diagnosis process of diabetes. This method enables the collection of patients' observed symptoms and medical information and applies predefined fuzzy rules to achieve accurate diagnoses. By continuously improving the implementation and development of more advanced expert systems, it is expected to discover more efficient and reliable solutions for diagnosing diabetes. The significant contribution of this research is expected to enhance the management of diabetes, improve the quality of life for patients, and mitigate the negative impact caused by this disease.